2017
DOI: 10.1111/flan.12266
|View full text |Cite
|
Sign up to set email alerts
|

Integration PCK: Modeling the Knowledge(s) Underlying a World Language Teacher's Implementation of CBI

Abstract: This case study enabled researchers to understand the knowledge embedded in a world language teacher's enactment of content‐based instruction (CBI) through the lens of a theoretical model inspired by Shulman's (1987) construct of pedagogical content knowledge (PCK). The model, called integration pedagogical content knowledge (I–PCK), represents an adaptation of PCK that explicitly addresses the expanded set of content knowledge that is necessary for teachers to effectively implement CBI. Through descriptions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…This tension has been theorized by Troyan et al (2017) as reflecting WL teachers’ need for ‘integrated pedagogical content knowledge’ (I-PCK). This model, building on Shulman’s pedagogical content knowledge (PCK) model (Shulman, 1987), in part frames the interplay between teachers’ content knowledge of language as a discipline (PCK-L), content knowledge of content that is not linguistic in nature (PCK-C), and the convergence of content knowledge about content and content knowledge about the second language (CK-L/C).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…This tension has been theorized by Troyan et al (2017) as reflecting WL teachers’ need for ‘integrated pedagogical content knowledge’ (I-PCK). This model, building on Shulman’s pedagogical content knowledge (PCK) model (Shulman, 1987), in part frames the interplay between teachers’ content knowledge of language as a discipline (PCK-L), content knowledge of content that is not linguistic in nature (PCK-C), and the convergence of content knowledge about content and content knowledge about the second language (CK-L/C).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…This model, building on Shulman’s pedagogical content knowledge (PCK) model (Shulman, 1987), in part frames the interplay between teachers’ content knowledge of language as a discipline (PCK-L), content knowledge of content that is not linguistic in nature (PCK-C), and the convergence of content knowledge about content and content knowledge about the second language (CK-L/C). Troyan et al (2017) argued that the success of CBI grows out of synergy between these related, but distinct types of knowledge when they become integrated. They suggested that WL teachers may need professional development to ‘cultivate a nuanced understanding of how to focus on content and form simultaneously’ (Troyan et al, 2017, p. 472).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, the gains of LCE are claimed to be largely dependent on the way teachers perceive, and implement it, especially that it is portrayed not to belittle the teacher's role but, rather, to multiply it (Ilieva, Wallace, & Spiliotopoulos, 2019;Van den Branden, 2016), a premise that maybe challenging to many teachers (Kaymakamoglu, 2018;Yamagata, 2018). In addition, previous studies have indicated that the implementation of LCE pedagogies requires high levels of awareness and specialized skills on behalf of teachers, together with encouraging school environments (Marwan, 2017;Shehadeh;Troyan, Cammarata, & Martel, 2017). Similarly, despite that several studies advocate that implementing LCE is challenging in terms of both course design and the development of instructional methods and materials (Bai & González, 2019;Philominraj, Jeyabalan, & Vidal-Silva, 2017), a number of research reports have shown that LCE has been successfully implemented even where teacher-centered instruction used to be the norm (Yu & Liu, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Content-based instruction (CBI), where nonlinguistic content is taught through the medium of a foreign language, has become very popular, especially in Europe, where it is known as content and language integrated learning (CLIL). Given that ACTFL has identified the integration of content and language as a research priority (Glisan & Donato, 2012) and that the implementation of CBI in language education is increasing (Troyan, Cammarata, & Martel, 2017), research on the use of CBI in foreign language teaching is an obvious growth area. 11 Notwithstanding what I have just written, research on language instruction includes not only language gains but also preventing language loss.…”
Section: The Porous Classroom Content-based Instruction and Prevementioning
confidence: 99%